2019
DOI: 10.20944/preprints201911.0168.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine Motor Precision Tasks: Sex Differences in Performance with and without Visual Guidance across Different Age Groups

Abstract: Previous studies have reported certain sex differences in motor performance precision. The aim of the present study was to analyse sex differences in fine motor precision performance for both hands in different tests conditions. 220 Spanish participants (ages: 12-95) performed fine motor tasks - tracing over the provided models – lines of 40 mm for both hands, two sensory conditions (PV – proprioceptive-visual; P – proprioceptive only) and three movement types (F – front… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This method goes back to Mira y López’s initial work, Las correlaciones somáticas del trabajo mental (somatic correlations of mental work) ( Mira, 1923 ), some insights of which were later developed in his hypothesis of individual differences in fine motor control. These ideas were confirmed experimentally by Mira y López’s own observation of pilots’ performance ( Liutsko, 2014 ), as well during his work with Luria’s polygraph ( Luria, 1932 ). This all contributed to creating the method of myokinetic psychodiagnosis (MKP) ( Mira, 1958 ).…”
Section: Methodsmentioning
confidence: 67%
See 3 more Smart Citations
“…This method goes back to Mira y López’s initial work, Las correlaciones somáticas del trabajo mental (somatic correlations of mental work) ( Mira, 1923 ), some insights of which were later developed in his hypothesis of individual differences in fine motor control. These ideas were confirmed experimentally by Mira y López’s own observation of pilots’ performance ( Liutsko, 2014 ), as well during his work with Luria’s polygraph ( Luria, 1932 ). This all contributed to creating the method of myokinetic psychodiagnosis (MKP) ( Mira, 1958 ).…”
Section: Methodsmentioning
confidence: 67%
“…In both cases we can speak of adaptive, favorable processes that occurred due to education, therapy, and/or medication. Moreover, high excitability does not always have a negative interpretation: People with a high IQ were also found with it ( Liutsko, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few studies have been conducted regarding the relationship between stress resilience and individual differences in proprioceptive accuracy of fine motor skills due to a general lack of 2 knowledge in the area of motor control in psychology. Draganova obtained, as a result of her PhD dissertation, named "Psychophysiological markers of the juvenile tolerance" (2007) (cited in [6]) the following myokinetical indicators [7] of the person with high tolerance: balanced processes of excitation and inhibition, normal emotional tone, absence of hetero-or auto-aggressiveness, and overall good myokinetic balance. The study by Şenol et al demonstrated that an increase in cortisol levels, associated with stress, negatively affects proprioception of the ankle joint, though significant differences were observed only with closed eyes [8].…”
Section: Introductionmentioning
confidence: 99%